Ganglioside GD3 May Suppress the Functional Activities of Benign Skin T Cells in Cutaneous T-Cell Lymphoma - Kume, Miki; Kiyohara, Eiji; Matsumura, Yutaka; Koguchi-Yoshioka, Hanako; Tanemura, Atsushi; Hanaoka, Yuma; Taminato, Mifue; Tashima, Hiroki; Tomita, Koichi; Kubo, Tateki; Watanabe, Rei; Fujimoto, Manabu (Frontiers in Immunology, 2021)
In cutaneous T-cell lymphoma (CTCL), which arises from skin-tropic memory T cells, malignant T cells and benign T cells are confined in the same skin lesions. It is thus difficult to evaluate the phenotypic characteristics and functional activities of benign T cells in CTCL. Disialoganglioside with three glycosyl groups (GD3) is increasingly expressed on the surface of solid malignant tumor cells and takes part in tumor progression and suppression of tumor immunity. However, the role of GD3 in CTCL is not well-understood. In this study, the malignant and benign T cells in CTCL skin lesions were distinguished by flow cytometry and their phenotypic characteristics were compared with those of T cells from control skin specimens. In CTCL skin lesions, the benign T cells included limited resident memory T cells (TRM), which are sessile in skin and known to exert strong antitumor function. The benign T cells showed diminished Th17 property, and the expression of GD3 was high in the malignant T cells. The expression of GD3 in the malignant T cells inversely correlated with IL-17A production from the benign CD4 T cells. GD3 from the malignant T cells was implied to be involved in suppressing the Th17 activity of the benign T cells independent of the regulation of TRM differentiation in CTCL. Revealing the role of GD3 in inhibiting the production of IL-17A in CTCL would aid the understanding of the suppressive mechanism of the antitumor activity by malignant tumor cells.